Portées théoriques et incarnations des valeurs épistémiques et ontologiques de la durabilité forte dans les politiques environnementales - Caroline Lejeune (Développement Durable et Territoires)
Strong sustainability is a concept that originates from the fields of ecological economics and environmental ethics. The pragmatist currents of environmental ethics and ecological economics have deepened what could be a conception of sustainability, taking into account thresholds of irreversibility and the finiteness of nature in the process of knowledge production. The concept of strong sustainability has therefore been formalized by bridging the gap between theory and environmental policy practice. However, the term “strong sustainability” has never been used as such in environmental public policies. The purpose of this article is to analyze the ontological and epistemic consideration of the concept of strong sustainability and its modes of embeddedness in environmental policies. We will study the consequences of scientific logics and the political effects of strong sustainability.